Finite-State Transducers for Oral Spelling Detection - Soares, Gabriel J. R.; Silva, José E. C.; Souza, Jairo F. de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
Reading fluency assessment plays a central role in early education systems worldwide. Countries such as the United States and Brazil administer large-scale oral reading assessments to monitor educational outcomes and guide intervention. However, most of the automatic assessments are often coarse in granularity. As a result, they are poorly equipped to handle children who do not yet decode words fluently and instead rely on spelling out individual letters or syllables. We show that finite-state transducers can be used to detect spelling to improve oral reading assessments. We demonstrate the effectiveness of our method on a corpus of annotated child speech, showing that it provides insight into early decoding strategies.